Educating Muslim Women: The West African Legacy of Nana Asma’u (1793-1864) By Jean Boyd and Beverly Mack Oxfordshire & Leicestershire: Interface Publications & Kube Publishing, 2013. 256 pages. (American Journal of Islam and Society, 2014)
Educating Muslim Women is a unique study of Muslim women told throughthe story of Nana Asma’u, a nineteenth-century Fulani woman from NorthernNigeria who became a renowned scholar and greatly impacted Muslim womenin Nigeria and beyond. Drawing on history, literary analysis, and ethnography,the volume’s slimness belies a wealth of material that will interest historians,applied linguists, and even sociologists of contemporary Muslim communities.The book’s main argument is that Muslim women have played a greaterrole in their communities than has previously been understood by historians.While using Nana Asma’u as an example, Boyd and Mack argue that she wasnot unique and offer painstaking details to show that her society supportedand encouraged female Islamic scholarship. In addition, they relate how contemporarywomen continue to follow her example. The book is organizedroughly chronologically, although the chapter titles suggest a thematic organizationthat is not always adhered to.The introduction offers some background on Sufism, which in later chaptersthe authors narrow down to the Qadiriyyah order. They define Sufism as“the prayerful pursuit of knowledge aiming to move an individual closer toGod” (p. 15). Their focus on knowledge allows them to emphasize Islamicscholarship and education: “Education, like Islam itself, was integral to allparts of daily life” (p. 21). Nineteenth-century schools are depicted as placeswhere pupils learned Qur’anic recitation and received religious blessings, aswell as practiced farming, obtained medical treatment, and sought personaladvice. By depicting education as central to Islam and Islam as central toNorthern Nigerian society, their subsequent account of how involved women ...